A self-healable polyvinyl alcohol-based hydrogel electrolyte for smart electrochemical capacitors. Issue 45 (3rd November 2016) - Wang, Zhikui; Tao, Feng; Pan, Qinmin
Abstract : A self-healable polyvinyl alcohol-based hydrogel electrolyte is synthesized for smart electrochemical capacitors with self-healing and tailorable characteristics. Abstract : This study reports a self-healable hydrogel electrolyte based on dynamic diol–borate ester bonding for smart electrochemical capacitors (ECs). The electrolyte is prepared via converting polyacrylic acid grafted polyvinyl alcohol (PVA- g -PAA) into a hydrogel in the presence of KCl and borax. The resulting PVA- g -PAA/KCl hydrogel electrolyte exhibits not only good flexibility but also high ionic conductivity up to 41 mS cm −1 . Interestingly, once the electrolyte is cut, it spontaneously restores its configuration, mechanical properties and ionic conductivity within 20 min. The self-healing process takes place at least 15 times under mild conditions without any external stimulus. Based on this unique capability, a smart electrochemical capacitor with self-healable and tailorable characteristics is assembled. The present investigation offers a novel strategy to synthesize self-healable hydrogel electrolytes that might be applied to flexible, wearable and smart energy-storage devices.